2023
DOI: 10.3389/fmed.2023.1191026
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic in diabetes and dyslipidemia management in a Spanish region: a retrospective study of the Aragon population

Rocio Mateo-Gallego,
Irene Gracia-Rubio,
María Carmen Garza
et al.

Abstract: IntroductionPrevious research has indicated that the COVID-19 outbreak had a negative impact on the diagnosis and management of cardiometabolic diseases. Our aim was to analyze the impact of the COVID-19 pandemic on the management of dyslipidemia and type 2 diabetes (T2D) in the Aragon region of Spain.MethodsWe conducted an observational retrospective study, which included data from all patients diagnosed with active T2D or dyslipidemia in Aragon during 2019–2021. Data was collected from the BIGAN platform, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…This contradicts the study of Rocio Mateo-Gallego, that revealed overload of the health system caused by the COVID-19 pandemic has resulted in an under diagnosis of T2D that might have increased hyperglycermia including undiagnosed T2D. (9) However, our present study revealed that increased HbA1c is associated with low levels of HDL in Diabetic patients in both males and females. A strong correlation was observed between glycated hemoglobin and Cholesterol and HDL levels in diabetic females.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This contradicts the study of Rocio Mateo-Gallego, that revealed overload of the health system caused by the COVID-19 pandemic has resulted in an under diagnosis of T2D that might have increased hyperglycermia including undiagnosed T2D. (9) However, our present study revealed that increased HbA1c is associated with low levels of HDL in Diabetic patients in both males and females. A strong correlation was observed between glycated hemoglobin and Cholesterol and HDL levels in diabetic females.…”
Section: Resultscontrasting
confidence: 99%
“…During the COVID-19 pandemic, the occurrence of high blood sugar decreases, but people dealing with type 2 diabetes face worsening blood sugar levels. This requires an increase in the use of medications to manage the situation (9) . Dyslipidemia maintains its grip, hovering at 23.5 percent prevalence in 2019 and 2020, inching upwards to 24.5 percent in 2021 (9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation